A Differential Game in Economics - Case, James (Management Science, 1971)
The problem of profit maximization for two firms manufacturing the same commodity is cast as a differential game. The qualitative aspects of the equilibrium point solution of the game are then discussed with the aid of some results on ordinary differential equations.